2017
DOI: 10.4172/2469-9764.1000122
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Alcalase hydrolysis conditions for production of Dagaa (Rastrineobola argentea) Protein hydrolysate with antioxidative properties

Abstract: Enzymatic conditions; stirring speed, pH, temperature, enzyme substrate (ES) ratio, solvent ratio, reaction time; for Dagaa (Rastrineobola argentea) hydrolysis by Alcalase 2.4L® were optimized. This was done to guarantee maximum enzyme activity, minimized losses and subsequent maximized product yield.This study showed optimized hydrolysis conditions to be fixed at minimum stirring speed (overhead stirrer, Stuart, UK), pH 7, 56°C, ES ratio of 2% (v/w) and solvent ratio of 0.5% (v/w) for 6 h. At these combined o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…In a previous research concerning the influence of enzyme concentration, time, temperature, and pH on DH of tuna fish viscera, it was shown that increasing Alcalase concentration from 1.0% to 1.5 %, temperature from Enzymatic hydrolysis has been used for proteins from various food sources to achieve the desired bioactivity and functional properties. Several reports have focused on producing bioactive peptides from fish proteins (Awuor et al 2017;Cheung et al 2012;Šližytė et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous research concerning the influence of enzyme concentration, time, temperature, and pH on DH of tuna fish viscera, it was shown that increasing Alcalase concentration from 1.0% to 1.5 %, temperature from Enzymatic hydrolysis has been used for proteins from various food sources to achieve the desired bioactivity and functional properties. Several reports have focused on producing bioactive peptides from fish proteins (Awuor et al 2017;Cheung et al 2012;Šližytė et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Rendemen hidrolisat miofibril belut lebih tinggi dibandingkan dengan hidrolisat dari daging merah tuna yaitu 1,21 g (Parvathy et al, 2018) namun lebih rendah dibandingkan dengan hidrolisat sarden mencapai 7,01 g (Jeevitha et al, 2014). Menurut Awuor et al (2017), perbedaan rendemen hidrolisat dapat dipengaruhi oleh tipe enzim dan substrat, kondisi hidrolisis (pH, suhu, lama hidrolisis, rasio substrat/enzim), dan rasio pelarut.…”
Section: Rendemen Hidrolisatunclassified
“…To obtain highly functional BAPs, it is necessary to optimize the hydrolyzation process [10]. The use of different types of proteases, substrates (different fish species/flesh/frame/viscera) and several other variables such as pH, time and temperature has been extensively investigated [11].…”
Section: Introductionmentioning
confidence: 99%